NILAI PENDIDIKAN KARAKTER DALAM KEGIATAN PEMBELAJARAN INFORMAL DIMASA PANDEMI DI DUSUN LUMBANG PENYENGAT - eviana; Fazira; Kiki Sundari; Naili Nur Fadzilah; Vivin Latif Suseno (CV Putra Publisher, 2022)
The pandemic period that has occurred at this time, of course, has had a huge impact on the world of education. One of them is a school with face-to-face learning which is currently abolished and replaced with online learning. Of course this also brings pros and cons among students and parents, lots of parents complain about the ineffectiveness of online learning for their children, to overcome these complaints one way or alternative that can be used is informal learning. . Informal learning carried out in Lumbang Penyengat Hamlet generally includes students from grade 1 to grade 6 SD. Studying in groups really brings a distinct impression for each student, especially in a pandemic like this. In the informal learning that is carried out not only learning about general education, but the learning program includes religious learning as well, such as the Koran, memorizing short suras, and so on.